AGRICULTURAL LAND CONVERSION IN JOGJAKARTA AN EMPIRICAL ANALYSIS - Mariyono, Joko (Jurnal Ekonomi & Studi Pembangunan, 2006)
Agriculture needs to exist because of ecological and economic reasons. Recently, the amount of agricultural lands tends to decrease inevitably because it has been converted to other businesses. This study aims to analyze agricultural land conversion in Jogjakarta using econometric models based on economic analysis. Panel data used in this study is compiled from five regions during period of 19 75-2000. Estimation is carried out using panel regression. The results show that agricultural lands decrease as transportation infrastructure increases. Wetland and dry land is convertible as the value of farmer exchange rate and population change. Wetland will be created as the farmer exchange rate increases, and will beconverted as population increases, and vice versa for the case of dry land. Dry land gets more economic and demographical pressure than wetland. As a result, dry land is converted more that wetland.